Pengaruh Biaya Promosi Terhadap Dana Pihak Ketiga Pada PT. Bank BRI Syariah Indonesia Tbk - Suhartono Suhartono; Suci Dwi Purwati; Taat Kuspriyono; Vera Agustina Yanti; Lukman Hakim (Akuntabilitas, 2022)
One way to increase third party funds is through promotion of bank services and products so that people are interested in saving their money at the bank. The purpose of this study is to analyze the effect of Promotional Costs on TPF. The sample data was taken from the BRI Syariah website for 2016–2020 monthly data analysis methods using statistical analysis of correlation, determination, and regression. The results showed that the relationship formed from two variables had a correlation coefficient of more than one and the direction of the relationship was positive, and the effect of promotion costs on third party funds was 0.038%. This figure was obtained from the results of the determination test. The regression equation formed between promotion costs and third party funds is = 26705681.242 + 203.726X.